Role of Kazakhstan in Regional Cooperation in Central Asia, 1991-2010: Exploring the Implications of Regional Collaboration in Central Asia (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Among the most notable developments in current foreign affairs are regional collaboration and integration. Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan, the Central Asian Republics, have joined large foreign organisations and agencies, such as the United Nations and the OSCE. However, in the sense of multilateral affairs in Central Asia (such as the Commonwealth of Independent States (CIS), the Collective Security Treaty Organization (CSTO), the Eurasian Economic Union (EEU), the Shanghai Cooperation Organization (SCO), the Silk Road Economic Belt, Central Asia plus the USA (C5 + 1), the EU Policy, Central Asia plus Japan, the Silk Road Economic Belt, Central Asia plus the USA (C5 + 1), there are obstacles, parallels and inconsistencies. Moreover, in Central Asia there is a connection between local – regional – global processes. Relevant local and international circumstances, as well as national and regional societies, traditions and ideologies, must be taken into consideration in definitions and explanations. The global world climate affects transitions. The present and potential development of Central Asia would be guided by the interconnection of local, international, trans-regional, and global issues and challenges.